Effects of Artificial Intelligence on Secondary and Higher Secondary Students (Grades 9–12) in District Khairpur Mirs: https://doi.org/10.5281/zenodo.16942380 - Mirza Muhammad Bilal Baig Mughal (`, 2025)
Artificial Intelligence (AI) is increasingly influencing education worldwide, offering tools for adaptive learning, automated assessment, and personalized feedback. While much research exists on AI integration in higher education and in technologically advanced nations, relatively little is known about its effects on secondary and higher secondary education in rural and semi-urban districts of Pakistan. This study examines the influence of AI on students in District Khairpur Mirs, a region representing the urban–peri-urban–rural divide in Pakistan’s Sindh Province. The research focuses on students from Grades 9–12 in six public and six private schools (N ≈ 600), including boys, girls, and co-educational institutions. Using a mixed-methods approach, the study collected survey responses from students, conducted focus group discussions, interviewed teachers and administrators, and observed classroom practices. The objectives were to assess the impact of AI on academic outcomes, explore student perceptions and readiness, identify challenges to adoption, and propose recommendations for policymakers and practitioners. Findings reveal that students perceive AI as particularly useful for English language learning and STEM subjects, where instant feedback and problem-solving support are most beneficial. However, access remains uneven, with private and urban schools reporting higher levels of exposure and confidence compared to public and rural schools. Challenges include limited internet connectivity, lack of devices, insufficient teacher training, and concerns about plagiarism and ethical misuse. The study concludes that while AI has the potential to enhance learning and empower students, its benefits are contingent upon infrastructure availability, teacher preparedness, and equity-focused policies. To maximize AI’s role in Pakistani education, targeted investments in connectivity, teacher professional development, AI ethics education, and localized curriculum integration are essential. Keywords: Artificial Intelligence in Education, Secondary Education, Pakistan, Khairpur Mirs, Digital Divide, Public vs. Private Schools, Equity, Teacher Training, Plagiarism, Student Perceptions